2016
DOI: 10.1111/os.12289
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Technique of Total Knee Arthroplasty without Soft Tissue Balance

Abstract: Total knee arthroplasty (TKA) without soft tissue balance can create a balanced knee to a mechanical axis of near neutral with bone cuts, and remove osteophytes thoroughly. In this study, the authors present detailed steps for performing TKA. The attached video demonstrates the TKA procedure. The patient is a 77-year-old man who had suffered from knee pain for 12 years. Physical examination showed the Apley test to be positive and that the range of motion (ROM) decreased. An X-ray filmed at the positive latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, some researchers have proposed that appropriate resection of the bone, meniscus and osteophytes (without the release of medial soft tissue) can restore good postoperative alignment in TKA [ 19 , 34 , 35 ]. After measuring the joint space of each procedure during TKA surgery, Yagishita et al [ 36 ] found that resecting medial osteophytes led to an increase of 1.9 ± 2.5 mm in the medial space in the extension position and 1.7 ± 1.6 mm in the flexion position, which in turn affected the postoperative alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers have proposed that appropriate resection of the bone, meniscus and osteophytes (without the release of medial soft tissue) can restore good postoperative alignment in TKA [ 19 , 34 , 35 ]. After measuring the joint space of each procedure during TKA surgery, Yagishita et al [ 36 ] found that resecting medial osteophytes led to an increase of 1.9 ± 2.5 mm in the medial space in the extension position and 1.7 ± 1.6 mm in the flexion position, which in turn affected the postoperative alignment.…”
Section: Discussionmentioning
confidence: 99%